2023
DOI: 10.1097/scs.0000000000009177
|View full text |Cite
|
Sign up to set email alerts
|

Facial Trauma Management During the Coronavirus Disease 2019 Pandemic

Abstract: Importance: Facial trauma is managed with open or closed treatment modalities; however, the impact of the coronavirus disease 2019 (COVID-19) pandemic on facial trauma management remains unclear. Objective: To determine whether the management of facial trauma varied during the COVID-19 pandemic. Design Setting, Participants: A retrospective review of 127 adults at The R Adams Cowley Shock Trauma Center at the University of Maryland between March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…The number of study participants/patients with mandible fractures is of a similar size to comparable studies in cranio-maxillofacial trauma centers. 27,30 Both the age distribution and the female: male ratio in the present study are comparable to the results of similar publications. 27,28 In the present study we saw a sharp decrease in mandible Regarding the fracture location, significant differences were only found for mandible ramus fractures in the present study (PC = 43.1%…”
Section: Discussionsupporting
confidence: 91%
“…The number of study participants/patients with mandible fractures is of a similar size to comparable studies in cranio-maxillofacial trauma centers. 27,30 Both the age distribution and the female: male ratio in the present study are comparable to the results of similar publications. 27,28 In the present study we saw a sharp decrease in mandible Regarding the fracture location, significant differences were only found for mandible ramus fractures in the present study (PC = 43.1%…”
Section: Discussionsupporting
confidence: 91%
“…For instance, with many recreational facilities and public spaces closed, people may be engaging in different types of activities at home, potentially leading to a shift in the causes of facial fractures. Similarly, the increase in work from home arrangements could potentially lead to a decrease injuries, including facial fractures [17][18][19]. This shift in epidemiology is clearly illustrated in the results of our study.…”
Section: Discussionsupporting
confidence: 56%
“…Second, closed reduction (including nasal bone reduction) mirrored the dynamics of nasal fractures, with an increase in percentage but undergoing a change in trend as a temporal dynamic. A report from the United States reported that during the COVID-19 pandemic, the clinical characteristics of patients with facial fractures remained unchanged, but the use of mandibulomaxillary fixation (MMF), a conservative treatment for mandibular fractures, decreased significantly 24 . However, the cause of the MMF decrease is considered to differ from the change in the dynamics of closed reduction (including nasal bone reduction) in Japan.…”
Section: Discussionmentioning
confidence: 99%